Making Composite Materials from Unsaturated Polyester and Coconut Fiber Judging from Mechanical Properties - Nurudin, Arif; Harmi Tjahjanti, Prantasi; Setyawan, Anton (Jurnal Improsci, 2024)
Making combined materials that consist of unsaturated polyester and coconut fiber is the target of this research. The samples were tested by tensile and hardness tests before and after warm-up, and obtained by the result was that the trend value of hardness of unsaturated polyester+coconut fiber experienced proportional degradation with the addition of the composition of coconut fiber. The composition of 3% coconut fiber+97% unsaturated polyester has the highest hardness value, reaching 46,7 kg/mm2, and downhill becomes 43,1 kgf/mm2 moment heated at a temperature of 500C for 1 hour. Analog to the tensile test, 3% coconut fiber + 97% unsaturated polyester composition has the highest ultimate tensile strength and yield point. Adding fiber can boost the elasticity modulus, but the warm-up treatment causes the expansion of coconut fiber. The result is that the value of the tensile and hardness of the polyblend will go downhill.